Adsorption kinetics of the ionic surfactant decanoic acid. (November 2016) - Casandra, Alvin; Lin, Ya-Chi; Liggieri, Libero; Ravera, Francesca; Tsay, Ruey-Yug; Lin, Shi-Yow
Highlights: Dynamic/equilibrium surface tensions of decanoic acid solutions were measured. Complete sets of ST relaxation curves were obtained using a pendant bubble tensiometer. The ionic generalized Frumkin model describes the ST relaxation data very well. A diffusivity of 5.5 × 10 −6 cm 2 /s was determinedfromthe dynamic surface tension data. Relaxation of the surface/sublayer properties [ Γ, ψ s, C1s, C1∞, and ψ ( r )] was reported. Abstract: The adsorption kinetics of ionic surfactant decanoic acid was examined. Dynamic and equilibrium surface tensions (ST) were measured using a video-enhanced pendant bubble tensiometer. The equilibrium ST data and the complete ST relaxation profiles were compared with theoretical profiles predicted by both non-ionic and ionic models. The quasi-equilibrium approach was used in the ionic model to describe the electric field in the electrical double layer. Both non-ionic and ionic generalized-Frumkin models predict the equilibrium and dynamic ST data very well. Using the ionic model, a comparison between the dynamic ST data and the theoretical ST profiles gave a diffusivity of 5.5 × 10 −6 cm 2 /s. The adsorption of decanoic acid onto the air–water interface was determined to be diffusion controlled. Dynamic surface properties ( Γ and ψ s ), the electrical potential ψ ( r, t ) in the double layer, and the double layer thickness λ ( C, t ) were also evaluated. It was found that the surface charge density increases very quickly at the early stages (∼1 s) of the surfactant adsorption process. Additionally, the electrical surface potential data implied that the surface charge density becomes significantly stronger at very dilute surfactant concentrations, where π is less than 1 mN/m.